2013
DOI: 10.1080/15389588.2013.794943
|View full text |Cite
|
Sign up to set email alerts
|

Road Safety from the Perspective of Driver Gender and Age as Related to the Injury Crash Frequency and Road Scenario

Abstract: According to the current study, based on the network approach for the allocation of economic resources and planning of road safety strategies, calibration of injury crash rate prediction models for specific target collision type is important because of the range of harms that are caused by different collision types. From these studies it is apparent that the age and gender of drivers considered together further refines how those factors contribute to crashes. Countermeasures (structural road interventions and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 16 publications
0
23
0
3
Order By: Relevance
“…This indicates that females are more careful and have lower risk taking attitudes than males. In terms of age, Russo et al (2013) again found that under wet-curved road surfaces in the night, drivers within the ages of 18-40 years have a higher risk of single-vehicle crashes whilst those within the ages of 20-45 years have higher risks for rear-end collisions in dry road surfaces at night at a tangent segment scenario.…”
Section: Gender and Age Variability In Traffic Attitudes And Violatiomentioning
confidence: 79%
See 2 more Smart Citations
“…This indicates that females are more careful and have lower risk taking attitudes than males. In terms of age, Russo et al (2013) again found that under wet-curved road surfaces in the night, drivers within the ages of 18-40 years have a higher risk of single-vehicle crashes whilst those within the ages of 20-45 years have higher risks for rear-end collisions in dry road surfaces at night at a tangent segment scenario.…”
Section: Gender and Age Variability In Traffic Attitudes And Violatiomentioning
confidence: 79%
“…Results for this study will therefore suggest the specific target group attitudes and behaviour that injury intervention programmes should focus on. Russo et al (2013) and Ulleberg and Rundmo (2003) posited that injury prevention programmes in developing countries are more likely to be successful when they are targeted at specific risk groups by a bottom-up approach rather than targeting the entire population.…”
Section: Gender and Age Variability In Traffic Attitudes And Violatiomentioning
confidence: 99%
See 1 more Smart Citation
“…From these studies it is apparent that the age and gender of drivers considered together further refines how those factors contribute to crashes. Countermeasures (structural road interventions and/or safety awareness campaigns) can be planned to reduce the highest rate of injury crash for each gender and road scenario: the awareness campaigns cannot be generalized or vague but must be organized by age and gender, because this study shows that crash dynamics alter as these factors change, with consideration for the varying psychological traits of the driver groups [10].…”
Section: Age Groupmentioning
confidence: 99%
“…The number of possible strategies for road safety improvements depend on the specific available resources at the time and they can be equal to the variables employed in the model on which it can actually work: before-after evaluations [17][18][19][20] allow us to check the safety benefits of improvements.…”
Section: Literature Reviewmentioning
confidence: 99%